3D PRINTING TECHNOLOGY: A CUSTOMIZED ADVANCED DRUG DELIVERY - PUND, ATUL; MAGAR, MANOJ; AHIRRAO, YOGESH; CHAUDHARI, ATUL; AMRITKAR, AMOL (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Three dimensional (3D) printing has emerged as one of the most promising additive manufacturing technology for producing 3D objects, with applications ranging from engineering prototyping to medications and cell-laden medical models. 3D printing techniques involve the deposition of materials such as thermoplastic polymers or hydrogel in sequential layers one on top of another to produce 3D object, regardless of the type, or underlying theory. The rapid rise in the number of published articles and patents in recent years indicates 3D printing’s current momentum in developing various drug delivery systems for pharmaceutical applications. While 3D printing techniques have a promising future, they must overcome a number of challenges before they can be used in commercial-scale production. The current ways of modifying drug delivery while making 3D printed dosage forms with different drug release patterns and properties are discussed in this review. These achievements are related to the delivery and development of patient-specific medicines. Major benefits of each type of 3D printing application, which are discussed; however, a critical review will show the limitations and constraints associated with 3D printing. Future research could focus on developing and adapting the techniques to suit with a wider range of materials. More emphasis on developing cost-effective printing technologies and compatible materials with these printers is needed to broaden the range of applications for 3D printed products.